What do we know about the future of food systems in Latin America and the Caribbean? - Piñeiro, Valeria; Hareau, Guy; Andrade, Robert (International Food Policy Research Institute, 2025)
Heterogeneity and inequality: Latin America and the Caribbean’s (LAC) agrifood systems are marked by significant disparities across the region and within countries in production, trade, and access to food, with inequality a central challenge. These disparities not only undermine food security but also hinder the region’s ability to develop sustainable and resilient food systems.